Wednesday

April 23, 2014

April 23, 2014

Posted by **coried** on Friday, July 24, 2009 at 11:34pm.

(49-x^2)^1/2 + 3x^2(49-x^2)^-1/2

________________________________

49 - x^2

- College Algebra -
**Reiny**, Saturday, July 25, 2009 at 7:21amcommon factor of (49-x^2)^(-1/2) at the top

= (49-x^2)^(-1/2)[49-x^2 + 3x^2]/(49-x^2)

= (49 + 2x^2)/(49 - x^2)^(3/2)

**Related Questions**

math115 - I have tried and tried I just do not get it 6-5(3x-4)=-49 6-15x+20=-49...

Algebra 2 - Can someone please assist me with this? (9/49)^(-3/2) I do this ...

maths - x^2-7x = 0 substitue x=7 into the equatiopn and explain why this shows ...

algebra 2nd try - I need to simplify this 2/∛49 . I figured it out to be (...

algebra - Simplify 2/root 3(49) I solved it as 2 root 3(49) over 49. the system ...

algebra - 1. the function f(x)=6x/3x-5 is one to one. find its inverse and check...

math - (3+4)^2= A-13 B-14 C-19 D-25 E-49 3+4=7 7X7=49 E-49

How do you properly distribute? - Can someone please show me (STEP BY STEP...

Physics - Four students measure the mass of an object, each using a different ...

physics - an arresting device on a carrier deck stops an airplane in 1.5s. the ...